Modelagem e simulação dinâmica de reatores de leito fixo - Rodrigues, Caroline (Universidade Federal de São Carlos, 2011)
This work investigated numerical methods in the solution of mathematical models of fixed-bed reactors. For the reactors modeling and simulation, two numerical methods were used: sequencing method (SM) and finite volume method (FVM). There were also proposed two mathematical models: the pseudo-homogeneous model and the dimensionless one, which is based on the Peclet (Pe) and Biot (Bi) numbers. A horizontal-flow anaerobic immobilized sludge (HAIS) reactor developed in bench scale and after a scale-up, reducing the COD in the wastewater treatment was simulated by sequencing method, varying the numbers of mesh; a tubular fixed-bed reactor with biomass immobilized for the startup period of lactic acid fermentation, also simulated by sequencing method and compared with experimental data; and was also evaluated the precision of sequencing and finite volume methods over the reactor s profile, varying the Peclet e Biot numbers. The models development was based on studies about hydrodynamics and biochemistry kinetics. Both methods described satisfactorily the behavior of the reactors in the performed simulations, but in high values of Peclet, the finite volume method generated inadequacies such as oscillatory responses and over the limit. This paper is an elucidation to sequencing method, which besides its huge range and simplicity, still is not so studied neither known, because it s a recent method.
Keywords: Reatores químicos (Engenharia química); Modelos matemáticos; Reator de leito fixo; RAHLF; Método da seqüência; Método dos volumes finitos; Mathematical model; Fixed-bed reactor; Horizontal-flow anaerobic immobilized sludge (HAIS) reactor; Sequencing method; Finite volume method; ENGENHARIAS::ENGENHARIA QUIMICA